Evaluating the Performance of Public Private Sector Dialogue Council in Regulation and Deregulation - Ahmad Markaz Malmiri (پژوهش‌های برنامه و توسعه)
Iran’s Public-Private Dialogue Council was established in 2011 according to article (75) of the Law for theFifth Development Plan. According to the law for the Continuous Improvement of Business Environment (Article 11 (a)) the Council was obliged to propose modification, abolishment or regulation or applying procedure to related officials in order to improve the business environment in Iran. According to the available content in the Council's website, the definite achievement of this council during 8 and a half years of activity on the grounds remarked was just modifying a procedure as a result of issuing a directive, modifying a directive and a regulation. Configuring agendas and enactments (of the Council), indicates that it has not been successful in regulation and deregulation. The council has not taken any action to get into modifying rules and the fact that it has not got much success in the cases contributed in regulation and deregulationreveals that there are many obstacles in performing this task which is the topic of this article. The main question of the present text is that, what are the reasons for the Council's failure in not getting any achievements in the functions of purpose, modification, abolishing or setting rules? This paper aims to answer this question without getting into the theoric analyse level and solely by functional analyses of the Council. The research method is based on the case study and a combination of documentary, normative and content analysis.